Effect of aminoethoxyvinilglycine (AVG) on preharvest fruit drop and maturity of apples - Amarante,Cassandro Vidal Talamini do (2002)
Apple trees cultivars Gala and Fuji were sprayed four weeks before commercial harvest with aminoethoxyvinilglycine (AVG), at doses of 0, 125, or 250 mg L-1, and assessed for preharvest fruit drop, fruit growth, and maturation on tree. In 'Gala', 64 days after AVG spraying, fruit drop for control treatment was 85%, and AVG (at 125 and 250 mg L-1) reduced it to 10%. In 'Fuji', 64 days after AVG spraying, fruit drop for control was 6%, while treatments with AVG (at 125 and 250 mg L-1) increased fruit drop to 10%. AVG was a powerful retardant of fruit maturation for 'Gala' but not for 'Fuji'. In 'Gala', the most affected attribute was the skin background color, followed, in decreasing order, by soluble solids content, the starch index, skin red color, the flesh firmness, and titratable acidity. In 'Gala', only flesh firmness retention was improved by increasing AVG dose from 125 mg L-1 to 250 mg L-1. The AVG at 250 mg L-1 inhibited "Gala" late fruit growth but not 'Fuji'.